(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Many European countries are very tiny and hence they have limited natural resources. Yet the people of these countries have exuberant and luxurious lifestyle leading to odd, unnecessary and excessive expenditure. This led these to find more market to meet out their expenditure and gain income .Thus they left their mother lands in search of new market, new place, establishing colonies and, spreading their religion, converting native, innocent people to their religion. By these ways they looted the natural resources of native (colonized) countries, and prepared ready made goods, sold to them at much higher prices. The kings and queens of the European countries sent the navigators almost to every nook and corner of the globe. Encouraged them to take part in this adventure with the honors, awards, knighthood, felicitation and provided them with other facilities. As a result Columbus discovered Caribbean countries (Now West Indies islands) Amérigo vespussy discovered America; Bartalomya dias found a new way to India, of which Vascodigama followed. Marco Polo went around the world. Subsequently many countries of Africa, Asia and America have fallen prey to Europeans tricks, tactics, cleverness treachery, glottenous, imperialism and Colonialism. Laws were passed in favor of Europeans /white men where there was no scope for free and fair trial for colonized people, no representation, no franchise and no promotion considering them as inferior and incapable.